MK591 (Quiflapon), a 5-lipoxygenase inhibitor, kills pancreatic cancer cells via downregulation of protein kinase C-epsilon - Monga, Jitender; Ghosh, Ritisha; Guddeti, Rohith; Chitale, Dhananjay; Khan, Gazala; Ghosh, Jagadananda (Frontiers in Oncology, 2024)
Introduction: Pancreatic tumors and cell lines derived from them exhibit elevated expression of 5lipoxygenase (5-Lox), whereas non-tumor glands or normal cells do not exhibit this overexpression. Arachidonic acid stimulates pancreatic cancer cell growth via metabolic conversion through the 5-Lox pathway, and inhibition of 5-Lox activity decreases the viability of pancreatic cancer cells. However, the downstream signaling mechanisms through which 5-Lox exerts its effects on the survival of pancreatic cancer cells remain to be elucidated.The effects of 5-Lox inhibition on cell proliferation, apoptosis, and invasive potential were investigated in pancreatic cancer cells. The protein expression was analyzed by western blot. Apoptosis was analyzed by Annexin-V binding assay and by detecting the degradation of chromatin-DNA to nucleosomal fragments. The protein kinase C-epsilon (PKCε) activity was measured by an immunoprecipitation-kinase assay. The in vivo effects of MK591 were evaluated in pancreatic tumor xenograft model.Results: MK591, a specific inhibitor of 5-Lox activity, killed pancreatic cancer cells via induction of apoptosis, involving externalization of phosphatidylserine, cleavage of PARP (poly-ADP ribose polymerase) and degradation of chromatin DNA to nucleosomes. MK591 effectively blocked in vitro invasion and soft-agar colony formation by pancreatic cancer cells and decreased pancreatic tumor growth in nude mice xenografts. Furthermore, inhibition of 5-Lox downregulated K-Ras and inhibited phosphorylation of c-Raf and ERKs. Interestingly, 5-Lox inhibition induced apoptosis in pancreatic cancer cells without the inhibition of Akt but the protein level of PKCε was dramatically downregulated. Furthermore, inhibition of 5-Lox decreased the phosphorylation of Stat3 at Serine-727. Pre-treatment of pancreatic cancer cells with peptide activators of PKCε prevented apoptosis induced by 5-Lox inhibition, suggesting that the mechanism by which 5-Lox inhibition causes cell death in pancreatic cancer involves downregulation of PKCε. The combination of low doses of MK591 and gemcitabine synergistically reduced the oncogenic phenotype and killed pancreatic cancer cells by inducing apoptosis.Discussion: These findings indicate that inhibition of 5-Lox interrupts an Akt-independent, PKCεdependent survival mechanism in pancreatic cancer cells and suggest that metabolism of arachidonic acid through the 5-Lox pathway plays an integral part in the survival of pancreatic cancer cells via signaling through PKCε, an oncogenic, pro-survival serine/threonine kinase.